Narrative Storytelling Culinary Speciality of Watugajah Community in Probolinggo Indonesia - Linda Laila Zahas Fana; Ari Ambarwati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to map and describe how the logic and important symbols of the Watu Gajah community are narrated in typical culinary storytelling. The Watu Gajah community has a cer-tain pattern in telling their special culinary. Culinary wealth that is told in a certain pattern is a strategic regional object for the promotion of culture (OPK) as a source of learning in Indonesian language learning. This study uses a descriptive qualitative approach to map and describe the meaning in the form of logic and symbols of the Watu Gajah community in telling their culinary storytelling. The data are the results of intense observations, structured and in-depth interviews about (1) how the logic of the Watu Gajah community is constructed in typical culinary storytelling and (2) how the symbols of the Watu Gajah community are used in typical culinary storytelling. This study utilizes a literary gastrocrit-ical lens to reveal the logic and symbols of the Watu Gajah community that correlate with gastronomy in the storytelling narrative of their typical food. The results of the study show that the typical culinary of the Watu Gajah community has various origin stories. From every name that can unite the Indone-sian people because these foods have previously been present and become the staple food of the Watu Gajah community which has now turned into traditional snacks in the market.